2010
DOI: 10.1177/070674371005500802
|View full text |Cite
|
Sign up to set email alerts
|

The Early Natural History of Bipolar Disorder: What We Have Learned from Longitudinal High-Risk Research

Abstract: Longitudinal high-risk research has provided convergent evidence that major mood and psychotic disorders often develop from nonspecific antecedents in predisposed people over time and development. For example, bipolar disorder (BD) appears to evolve from nonspecific childhood antecedents, including anxiety and sleep problems, followed by adjustment and minor mood disturbances through early adolescence, culminating in major mood episodes in later adolescence and early adulthood. Therefore, the current cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 68 publications
(83 reference statements)
5
70
0
11
Order By: Relevance
“…Considering such findings, it is plausible to suggest that childhood adversity may be related to increased vulnerability to BD symptoms during development. Keeping this in mind is crucial, as high-risk longitudinal studies have highlighted the heterogeneity of mood disorders during development and provide evidence of the evolution of psychopathology across the time (43,44). Because the studies included in this review evaluated childhood trauma retrospectively, conclusions about cause and effect are not possible and issues about memory bias should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering such findings, it is plausible to suggest that childhood adversity may be related to increased vulnerability to BD symptoms during development. Keeping this in mind is crucial, as high-risk longitudinal studies have highlighted the heterogeneity of mood disorders during development and provide evidence of the evolution of psychopathology across the time (43,44). Because the studies included in this review evaluated childhood trauma retrospectively, conclusions about cause and effect are not possible and issues about memory bias should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, clinical course, environmental factors, family history, and treatment response are not considered in the current diagnostic classification systems (44). Assuming that childhood abuse and neglect could accelerate the evolution of BD or may impact its pathophysiology, the incorporation of early life trauma in diagnostic and treatment decisions may assist in BD treatment planning and prognosis, emphasizing the imperative need of early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…50,58,[72][73][74] Specifically, children of parents with BD with an excellent response to long-term lithium (lithium responders) had a completely normal or gifted early developmental course. In contrast, the children of parents who failed to respond to lithium prophylaxis (lithium nonresponders) manifest childhood problems with cognition, emotional regulation, socialization, and neurodevelopmental disorders.…”
Section: Clinical Staging: Prospective High-risk Studiesmentioning
confidence: 99%
“…For example an exclusionary clause might be created i.e., in the presence of childhood ADHD, more symptoms might be required, or "irritability" might be excluded as an A criterion. More longitudinal research is required, both of patients first identified by manic symptoms (e.g., LAMS), and of those first identified with ADHD, if we are to fully understand what symptoms should characterize "true" BD or its variants across development, in view of longitudinal studies of highrisk children from parents with BD [45] . These studies indicate that emerging BD is not characterized by early onset irritability or ADHD, but instead by unfolding anxiety symptoms and sleep disturbances, before the first manic or hypomanic episode.…”
Section: Yesmentioning
confidence: 99%